The Traditional Market Development Strategy in North Sumatra with an Islamic Economic Perspective - Rahmani, Nurahmadi Bi; Aslami, Nuri; Tambunan, Khairina (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
There are various types of traditional market revitalization taking place in Indonesia, and not all traditional markets are successful after being revived. One of the reasons why not all old markets are successful after revitalization in Indonesia is because there are no guidelines or standards for revitalization. This research aims to see how traditional market development strategies exist in North Sumatra. The method used is SWOT with data collection techniques in the form of in-depth interviews and focus group discussions. Participants in this research were related government agencies, related agencies, academics, and consumers of traditional market traders. The weaknesses of traditional markets in North Sumatra are the inappropriate market location, inadequate facilities and sanitation, lack of use of digital markets and online transactions. The obstacles are the lack of orderly culture in society in carrying out trade transactions in traditional markets, the existence of extortion, and the existence of modern markets. For strength, namely being able to provide awareness of orderly shopping, being able to create clean and safe traditional markets, and maintaining local wisdom. The opportunities available include support from the local government and related agencies, technological developments, and digital market developments. This research recommends that there is a need for appropriate regulations and sustainable programs for the development and existence of this traditional market.